DESIGN OF FLUE GAS DESULFURIZATION IN AIR POLLUTION CONTROL SYSTEM OF SUMSEL 8 POWER PLANT - HAFIZHAH NIM: 15314074, HAURA
Sumsel 8 Power Plant has a production capacity of 2x660 MW and is located in Muara Enim, South Sumatra. The coal requirement for 1 unit of boiler is 357,2 tons/hour with the sulphur content in coal is 0.5%. The result of SO2 gas estimation based on stoichiometric approach is 1.599,886 mg/Nm3. This concentration exceeds the SO2 gas emission quality standard for the power plant listed in Annex IB Regulation of the Ministry of Environment Number 21 Year 2008, which is 750 mg/Nm3. The release of high concentration of SO2 into the atmosphere will have a potential to change ambient air quality, that will have negative impacts on human health and the environment. Therefore, the Flue Gas Desulfurization (FGD) unit will be used as a SO2 removal unit. The type of FGD used is a limestone scrubber, which is designed to achieve 95% removal efficiency, which is a typical maximum efficiency that a limestone scrubber can achieve. The FGD unit consists of reagent processing units, which are limestone silo and slurry tank, a scrubber, and sludge treatment units, which are thickener and belt presses. In the scrubber internal, packing material (Berl Saddle type with ceramic material and 2 inch diameter) will be used. For flue gas flow of 2.075.256,73 kg/hour, L/G ratio required is 35,8 gal/1000 acf with limestone feed rate of 4.147,475 kg/hour. From the design result, the diameter and height of scrubber are 17,5 m and 20,5 m respectively.